2004
DOI: 10.1021/np0400611
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Glycosmis arborea:  Three New Carbazole Alkaloids and Their Biological Activity

Abstract: As part of the phytochemical studies of the plant genus Glycosmis, the constituents of the plant Glycosmis arborea were investigated. Three new carbazole alkaloids named glybomines A (1), B (2), and C (3), along with known monomeric alkaloids belonging to the carbazole, quinazoline, furoquinoline, quinolone, and acridone classes, were isolated from stems of the plant collected at Mymensing in Dhaka, Bangladesh. Glybomine A (1) is the first example of a 2,5-oxygenated carbazole alkaloid from natural sources. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…Hepatoprotective activity of butanol extract of aerial parts is reported (Gomes et al, 2003). The carbazole and acridine alkaloids isolated from Glycosmis arborea were reported to have inhibitory activity over Epstein-Barr virus (Ito et al, 2004) and anti-tumor activity (Quader et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatoprotective activity of butanol extract of aerial parts is reported (Gomes et al, 2003). The carbazole and acridine alkaloids isolated from Glycosmis arborea were reported to have inhibitory activity over Epstein-Barr virus (Ito et al, 2004) and anti-tumor activity (Quader et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The present study was aimed at studying the effect of the leaves of the plant on breast cancer cell lines. Previous studies on the plant reported the presence of acridone and carbazole alkaloids (Ito et al, 2004;Quader et al, 1999). Carbazole alkaloids also can intercalate the DNA due to their polycyclic and aromatic nature (Asche and Demeunynck, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They possess a variety of biological effects; viz the acridone alkaloids from G. arborea including atalaphyllidine, 5-hydroxy-N-methylseverifoline, atalaphyllinine, and des-N-methylnoracrony-cine showed potent antiproliferative activity against tumor cell lines [22]. Along with acridones, monomeric alkaloids belonging to the carbazole, quinazoline, furoquinoline and quinolone exhibited significant anti-tumor-promoting activity on Epstein-Barr virus early antigen activation [23]. Glycosmicine, one derivative of quinazolinedione has been isolated from the G. arborea.…”
Section: Introductionmentioning
confidence: 99%